Peningkatan Jiwa Entrepreneur Karang Taruna Melalui Penyuluhan Diversifikasi Olahan Jamur Tiram - Novita Lidyana; Dyah Ayu Perwitasari; Linda Kurnia Supraptiningsih (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
Karang Taruna Sukokerto Pajarakan Village Probolinggo Business skills owned by youth Karang Taruna Sukokerto Village Pajarakan District is still relatively limited, because it has never obtained assistance from competent parties in the field of entrepreneurship. In fact, when viewed from their relatively productive age, they have the potential to develop in creative entrepreneurial activities according to young souls for cadet corals. Karang Taruna organization that participated in this activity amounted to 20 people. The purpose of community service carried out by lecturers of Panca Marga Probolinggo University is to improve the soul of enterprenuer Karang Taruna Sukokerto subdistrict Pajarakan held extension of diversity of processed diversity made from tiram mushrooms. In this activity, counseling is able to foster intentions for cadet corals in Sukokerto Village, Pajarakan Subdistrict for entrepreneurship because the process of diversifying processing made from oyster mushrooms is easy to remember and easy to do so that after this extension activity ends up participants have the most advanced knowledge and skills[at diversification of product processing itself and can sell products online simply which can later grow entrepreneurial spirit. The resulting products are krispy mushrooms, mushroom satay and mushroom grilled rice. In addition to making various processed, also given skills in marketing online. Keywords: diversification of oyster mushrooms, Karang Taruna